Effects of chilling tolerance induced by spermidine pretreatment on antioxidative activity, endogenous hormones and ultrastructure of indica-japonica hybrid rice seedlings - Yan-hua ZENG; Yu-ping ZAHNG; Jing XIANG; Hui WU; Hui-zhe CHEN; Yi-kai ZHANG; De-feng ZHU (Journal of Integrative Agriculture, 2016)
Abstract: Spermidine (Spd) is known to be involved in the regulation of plant responses to chilling stress and counteract the adverse effect of stress conditions. Antioxidant activities, endogenous hormones and ultrastructure change under chilling stress were investigated in indica-japonica hybrid rice seedlings. 12-d-old seedlings were subjected to exogenous Spd (1 mmol L−1) and then a chilling stress (6°C, 4 d) was induced, followed by a subsequent recovery (25°C, 4 d). Results showed that malondialdehyde (MDA) and proline content were enhanced significantly, whereas shoot fresh and dry weights decreased during chilling stress and after recovery; chlorophyll content of chilling-stressed seedlings increased slightly but declined after recovery; additionally, total soluble sugar, sucrose, fructose and starch contents increased significantly during chilling stress, and only soluble sugar and fructose contents were observed in increase after recovery; chilling stress-induced increases in superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities, but declined after recovery, and the level of ascorbate peroxidase was lower during chilling stress and after recovery; however, endogenous indole-3-acetic acid (IAA), zeatin riboside (ZR), gibberellic acid (GA3), and abscisic acid (ABA) levels were induced decreased compared with Spd pretreatment. The microscopic analysis revealed that chilling stress-induced destruction of the chloroplast envelope during chilling stress and increased the number of plastoglobuli along with aberrations in thylakoid membranes after recovery. In contrast, exogenous Spd protected rice seedlings from chilling-induced injuries in terms of lower malondialdehyde, proline and carbohydrates accumulation coupled with increased endogenous hormones metabolism. After recovery, Spd pretreatment chilling-exposed seedlings showed higher activities of antioxidant enzymes and normal physiological function of chloroplasts. These results suggest that Spd could promote effectively chilling tolerance which might be largely attributable to the integrity of cell structure and normal metabolism of endogenous hormones in indica-japonica hybrid rice seedlings.